1994
DOI: 10.1002/etc.5620130205
|View full text |Cite
|
Sign up to set email alerts
|

Chemical fate and transport in a domestic septic system: Sorption and transport of anionic and cationic surfactants

Abstract: The sorption and transport of linear alkylbenzene sulfonate (LAS) and dialkyl quaternary ammonium compounds [ditallow dimethyl ammonium chloride (DTDMAC) and distearyl dimethyl ammonium chloride (DSDMAC)] were determined within the upper soil horizons and in the aquifer below a septic tank tile field at a study site in Ontario. Sorption of LAS was greatest immediately below the tile field (Kd = 17 L/kg) within the upper unsaturated soil horizons and lowest in the aquifer (Kd = 1 L/kg). LAS sorption appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…A nearly identical range of partition coefficients was determined with C 12 LAS in sediments containing 0.6 to 2.9% TOC [23]. Other studies with LAS have shown K app ranging from 1 to 3,000 L/kg [2,5,14,24,25]. The amount of sorption (as measured by the apparent partition coefficient) correlated well with the fraction of organic carbon in the sediment (R 2 ϭ 0.85).…”
Section: Equilibrium Partitioning Theory Describes the Sorption Of Absupporting
confidence: 61%
“…A nearly identical range of partition coefficients was determined with C 12 LAS in sediments containing 0.6 to 2.9% TOC [23]. Other studies with LAS have shown K app ranging from 1 to 3,000 L/kg [2,5,14,24,25]. The amount of sorption (as measured by the apparent partition coefficient) correlated well with the fraction of organic carbon in the sediment (R 2 ϭ 0.85).…”
Section: Equilibrium Partitioning Theory Describes the Sorption Of Absupporting
confidence: 61%
“…In addition, little has been published on the fate and transport of pharmaceuticals in the unsaturated and saturated zones (Drewes et al 2003;Heberer and Verstraeten in press). Organic compounds can be biodegraded in the subsurface, especially in an aerobic medium, leading to a wide variety of degradates (Drewes et al 2003;McAvoy et al 1994;Robertson 1994;Vengosh et al 1994;Verstraeten et al 2002aVerstraeten et al , 2002bVerstraeten et al , 2003. On the other hand, anaerobic or suboxic conditions, which can exist near septic fields, could prevent or slow down the degradation of organic compounds in ground water.…”
Section: Organic Compoundsmentioning
confidence: 99%
“…The subsurface soils at Cambridge contain 95% sand and only 0.5% clay [6], most of which is smectite [41]. As expected from the low clay content, the measured CEC of these soils averages only 5.0 meq/100 g [6].…”
Section: Cation Exchangementioning
confidence: 99%